2012
DOI: 10.1208/s12248-012-9445-3
|View full text |Cite
|
Sign up to set email alerts
|

The Twofold Advantage of the Amorphous Form as an Oral Drug Delivery Practice for Lipophilic Compounds: Increased Apparent Solubility and Drug Flux Through the Intestinal Membrane

Abstract: Abstract. The purposes of this study were to assess the efficiency of different nifedipine amorphous solid dispersions (ASDs) in achieving and maintaining supersaturation and to investigate the solubilitypermeability interplay when increasing the apparent solubility via ASD formulations. Spray-dried ASDs of nifedipine in three different hydrophilic polymers, hydroxypropyl methylcellulose acetate succinate (HPMC-AS), copovidone, and polyvinylpyrrolidone (PVP), were prepared and characterized by powder X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…These opposing effects on apparent solubility and permeability must be taken into account in order to fully understand the impact on the overall fraction of drug absorbed when solubility-enabling formulations are employed to enhance the oral exposure of a poorly soluble drug. We have recently revealed that the solubility-permeability tradeoff can be circumvented by using amorphous solid dispersions that increase the apparent solubility of the drug by supersaturation (and not solubilization), provided substantial supersaturation can be achieved and maintained [39], [40]. However, the development and manufacture of these solubility enabling formulations are much more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…These opposing effects on apparent solubility and permeability must be taken into account in order to fully understand the impact on the overall fraction of drug absorbed when solubility-enabling formulations are employed to enhance the oral exposure of a poorly soluble drug. We have recently revealed that the solubility-permeability tradeoff can be circumvented by using amorphous solid dispersions that increase the apparent solubility of the drug by supersaturation (and not solubilization), provided substantial supersaturation can be achieved and maintained [39], [40]. However, the development and manufacture of these solubility enabling formulations are much more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the studies on the relationship between membrane transport and supersaturation have been in the context of transdermal delivery, there is an increasing interest in exploiting supersaturated solutions to enhance oral absorption. Recent studies have demonstrated enhanced flux across intestinal membranes when perfused with supersaturated solutions . However, the impact of the colloidal species generated in highly supersaturated solutions has not been fully evaluated to date.…”
Section: Introductionmentioning
confidence: 99%
“…This solubility–permeability tradeoff was shown in several settings, including cases in which the increased solubility is accompanied by decreased free fraction that can explain the decreased permeability, but also in cases that do not involve decreased free fraction of the drug . It was recently discovered that this tradeoff can be overcome by using the amorphous form of the drug for solubility enhancement via supersaturation …”
Section: Introductionmentioning
confidence: 99%